The Challenge of Implementing Corporate Social Responsibility in Sustainability Certified Palm Oil Mills (Case Study PT X and PT Y) - Winarti, Rachel Yessica; Siagian, Yolanda Masnita; Utha, Maria Ariesta (Green Publisher Indonesia, 2023)
CSR is the company's responsibility for the impact of its activities and decisions on society and the environment. Implementation of CSR guided by the principles of ISO 26000 can optimize CSR efforts in the company. CSR has an important role in improving people's welfare and reducing environmental impact, but the implementation of CSR is still not optimal. This shows that palm oil mills need to make improvement efforts so that CSR implementation becomes more optimal, the research aims to determine the challenges in implementing CSR programs and provide recommendations to overcome dominant challenges. This research used delphi methods to assess the relevance of challenge and TOPSIS methods for prioritize the challenge. The first step in formulating improvement efforts is identifying the challenging factors in CSR implementation. The Delphi method aims to assess the relevance of challenges; the Delphi results show one additional challenge: